Reforma y contrarreforma laboral en Argentina, crónica simple de un proceso pendular - Goldin, Adrián (Pontificia Universidad Católica del Perú. Fondo Editorial, 2012)
Labor reform and counter-reform in Argentina, simple chronic of a pendulum processAfter placing it in the context of the processes of labor reforms produced in Latin America in the early 90’s (its inspiration, its dynamics, its actors), the article considers in particular the case of Argentina. Inthat assignment, it examines the labor reforms that took place there from dominant perspectives - external flexibility, internal flexibility, reduction and variation of costs, collective labor relations - confirming a strong deregulated activism in the field of individual relations, while it was verified a high administrative interventionism of decentralized bias with a limited institutional transformation in collective relations.At the end of that decade, it had already been clear that those strategies haven’t had a virtuous effect on the social labor situation or the labor market. In this context, a new government that comes into power in 2003, leaves without effect a good part of those reforms and instead it undertakes a process of institutional reconfiguration of the legal system of labor protection: a systematic increase of the Living Wage, strengthening of the collective wage bargaining - with the consequent tendential improvement of wages of workers in the formal sector - and, by virtue of parliamentary initiatives, a sequence of introduction of micro-reforms always oriented to increase the protection of workers, which as a whole would have to involve a remarkable recovery of the tutelary bias of labor regulations.

El artículo analiza la reforma argentina en el contexto de los procesos de las reformas laborales producidas en América Latina en la década de los noventa (su inspiración, su dinámica, sus actores). En ese cometido, examina las reformas laborales que tuvieron lugar allí desde las perspectivasdominantes —la flexibilidad externa, la flexibilidad interna, la reducción y variabilización de los costos, las relaciones colectivas del trabajo— constatándose un fuerte activismo desregulador en el campo de las relaciones individuales, en tanto se verificaba un alto intervencionismo administrativo de sesgo descentralizador con escasa transformación institucional en el de las relaciones colectivas.Al final de aquella década había quedado ya en evidencia que esas estrategias no habían tenido un efecto virtuoso sobre la situación socio-laboral ni sobre el mercado de trabajo. En ese contexto, un nuevo Gobierno, que accede al poder en 2003, deja sin efecto buena parte de aquellas reformas y emprende en cambio un proceso de reconfiguración institucional del sistema legal de protección del trabajo: incremento sistemático del Salario Mínimo Vital, fortalecimiento de la negociación colectiva salarial —con la consiguiente tendencial mejora de los salarios de los trabajadores del sector formal– y, envirtud de iniciativas parlamentarias, una secuencia de introducción de microreformas siempre orientadas a intensificar la protección de los trabajadores que en su conjunto habrían de implicar una notable recuperación del sesgo tutelar del ordenamiento laboral.
Keywords: Reformas laborales; América Latina; Argentina; Flexibilidad externa; Flexibilidad interna; Contrarreforma laboral; https://purl.org/pe-repo/ocde/ford#5.05.00